Tarnobrzeska Specjalna Strefa Ekonomiczna Euro-Park Wisłosan w latach 1997-2007 - Kozaczka, Marian (Przegląd Prawno-Ekonomiczny, 2007)
Streszczenie dostępne wyłącznie w języku angielskim: Special Economic Zones (SEZ) stand for the areas separated out of the rest of Poland and allocated for business activity on preferential terms and conditions. Such zones are subject to special administrative treatment. Pursuant to some acts and secondary legislature, numerous allowances and tax exemptions apply to investors who make investments there. SEZs changed the economic image of many regions in Poland. Various domestic and foreign companies appeared there. Their infrastructure was developed. Demand for building, security and cleaning services grew. The role of SEZ in the economic growth of Poland is significant and it will even grow in the nearest future.